Postnatal Development of Splenic Stroma in Indian Domestic Pig (Sus scrofa domesticus) - Harshini, Muppidi; Rajendranath, Nalla; Kumar, Sundari Ranjith; Rao, Jorige Radha Krishna (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The study was conducted on spleen of 18 healthy pigs (6 each of 0-4 weeks, 4-10 weeks and above 10 weeks of age) to evaluate the postnatal development. The sections were processed and stained to obtain the histological details. The spleen consisted of stroma and parenchyma. The stroma was composed of capsule and trabeculae. Microscopic details obtained by staining with H&E, Van Gieson, Verhoeff, Masson trichome revealed that splenic capsule was thick with two layers, viz., an outer dense irregular fibrous connective tissue layer and inner smooth muscle layer. Collagen fibers were predominant over elastic and reticular fibers. Trabeculae extended from the capsule dividing the splenic parenchyma into compartments and served as a frame work to support muscle, collagen, elastic and reticular fibers. The collagen, elastic, reticular and smooth muscle fibers increased with age. There was also a significant increase in trabecular branching, capsule thickness as the age progressed.